Performance and carcass characteristics of yearling steers and heifers fed Agrado™ throughout the finishing period - Sindt, J.J.; Dicke, B.; Klopfenstein, T.J.; Borck, L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A finishing experiment was conducted at a commercial feedlot facility in Larned, Kansas, using 3,295 yearling steers and heifers to evaluate effects of Agrado™ addition to finishing diets. Agrado (ethoxyquin) is a dietary anti-oxidant that protects against oxidative loss of critical vitamins and prevents rancidity and unpalatable odors. Supplementing finishing diets of yearling steers and heifers with 150 ppm Agrado had no measurable effects on growth performance or carcass characteristics.
Keywords: Beef; Performance; Carcass characteristics; Steers; Heifers; Agrado™